Spinal Nerve Roots Abnormalities on MRI in a Child with SURF1 Mitochondrial Disease - Rubino, Alfonso; Bruno, Giorgia; Mazio, Federica; de Leva, Maria Fulvia; Ruggiero, Lucia; Santorelli, Filippo Maria; Varone, Antonio (Neuropediatrics, 2021)
Variants in SURF1, encoding an assembly factor of mitochondrial respiratory chain complex IV, cause Leigh syndrome (LS) and Charcot-Marie-Tooth type 4K in children and young adolescents. Magnetic resonance imaging (MRI) appearance of enlarged nerve roots with postcontrastographic enhancement is a distinctive feature of hypertrophic neuropathy caused by onion-bulb formation and it has rarely been described in mitochondrial diseases (MDs). Spinal nerve roots abnormalities on MRI are novel findings in LS associated with variants in SURF1. Here we report detailed neuroradiological and neurophysiologic findings in a child with LS and demyelinating neuropathy SURF1-related. Our case underlines the potential contributive role of spinal neuroimaging together with neurophysiological examination to identify the full spectrum of patterns in MDs. It remains to elucidate if these observations remain peculiar of SURF1 variants or potentially detectable in other MDs with peripheral nervous system involvement.
Keywords: Leigh syndrome; spine MRI; inherited peripheral neuropathy; mitochondrial diseases; SURF1